Yield and Fatty Acid Profile as Affected by Sowing Date and Seed Rate of Linseed (Linum usitatuissimum L.) Under River Nile State Environment (University of Khartoum Journal of Agricultural Sciences, 2025)
linseed is rich in oil and fatty acid content, both of which vary greatly with the environment. The objective of this experiment was to determine the optimum planting date and seed rate of linseed as a potential crop for the existing cropping system of River Nile state. Four sowing dates (first of November, mid November, first of December and mid December) and three seed rates (50, 60,and 70 kg/ha ) were studied in an experiment carried out in Hudeiba Research station farm for two winter seasons ie 2011/2012 and 2013/2014. The experiment was laid out in split plot design with three replications. Seed rates were randomized in the main plots and sowing dates in subplots. Results showed that seed yield was not significantly affected by seed rate but by sowing date.. First of November sowing date with 60kg/ha seed rate resulted in the highest seed yield of 1216 kg/ha; seed yield declined with delaying sowing. The highest oil content (20.8%) was obtained from planting at 50 kg/ha in first of November. A total of twenty fatty acids were identified in different sowing dates . Number of fatty acid varied from one sowing date to another. That is, 15 in First November, 7 in mid November, 8 in First of December and 14 in mid of December sowing. Dominant fatty acids in first of November, mid November, first of December and mid December sowing dates were oleic acid, linolelaidic acid, linolelaidic acid and oleic acid respectively.
Keywords: Flaxseed; cultural practices; linseed; oil content